Medical genetics and genomics training in obstetrics and gynecology residencies: are we ready for the future?*. (3rd April 2019) - Putra, Manesha; Idler, Jay; Dai, Jing; Blitzer, Miriam G.; Feldman, Gerald; Sokol, Robert J.
Abstract: Objective: The primary objective of this study is to evaluate the availability and duration of formal medical genetics and genomics (MGG) education during obstetrics and gynecology (OB/GYN) residency training in the United States compared to other noncore OB/GYN rotations. Methods: We performed a review of rotation schedules published in all American Council for Graduate Medical Education (ACGME)-accredited OB/GYN residency programs' websites during the month of December 2016. Information regarding availability and duration of MGG rotation and other noncore OB/GYN rotations (ultrasound, breast health, and family planning) were collected. Results: Among 256 ACGME-accredited OB/GYN residency programs, rotation schedule was available for 238 (93%). Only 34 programs (14.3%) had some form of MGG rotations. In the GLM, when compared to other noncore OB/GYN rotations, the mean duration of MGG rotation was significantly less than ultrasound (0.07 versus 0.57 months, p < .05) and family planning (0.07 versus 0.42 months, p < .05). The number of residents was the only variable significantly correlated with the availability of an MGG rotation (OR 1.07, 95%CI 1.02–1.13). Conclusions: Despite the growing importance of MGG in day-to-day OB/GYN practice, only a limited number of ACGME-accredited OB/GYN residency programs offer an MGG rotation. When compared to other noncore OB/GYN rotations, such as, ultrasound and family planning, any MGG rotation was significantly shorter. With clear evidence that MGG will continue to radically change practice of OB/GYN in the future, it is imperative that steps need to be taken to address this deficiency in training.